Pharmacological interventions for periorificial (perioral) dermatitis in children and adults: a systematic review. (2nd December 2021) - Gray, N.A.; Tod, B.; Rohwer, A.; Fincham, L.; Visser, W.I.; McCaul, M.
Abstract: The plethora of pharmacologic treatments used for periorificial dermatitis (POD) makes clinical decision‐making challenging. The objectives of this review were to assess the efficacy and safety of pharmacological interventions for POD in children and adults. The search was performed on 2 February 2021 and included seven databases and trial registries, with no date or language restrictions Study selection, data extraction and risk of bias assessments were performed independently and in duplicate by two authors, in accordance with a prespecified protocol. Meta‐analyses were performed and reported in accordance with PRISMA guidelines. Where meta‐analysis was not possible, a narrative synthesis was performed and reported in accordance with SWiM guidelines. The certainty of evidence was assessed using the Grading of Recommendation, Assessment, Development and Evaluation approach. Eleven studies representing 733 participants were included. Oral tetracycline may improve physician‐reported severity of POD from day 20 onwards (low certainty evidence). Adverse effects may include abdominal discomfort, facial dryness and pruritus. Pimecrolimus cream may improve physician‐reported severity slightly after 4 weeks of treatment (MD −0.49, 95% CI −1.02 to 0.04, n  = 164, low certainty evidence). Adverse effects may include erythema, herpes simplex virus infection, burning and pruritus. Azelaic acid gel may result in no change in either physician‐ or patient‐reported severity after 6 weeks of treatment. The evidence is very uncertain about the effect of praziquantel ointment on physician‐reported severity and skin‐related quality of life after 4 weeks of treatment. The evidence is also very uncertain about the effect of topical clindamycin/benzoyl peroxide on physician‐reported severity. The body of evidence to inform treatment of POD currently consists of low and very low certainty evidence for important outcomes. Well‐designed trials are needed to further investigate treatment options. Data are required for children and from low‐middle income countries to improve external validity. Future trials should also include adequate post‐treatment follow‐up and standardized outcome measures.